Perancangan dan Pembuatan Aplikasi Administrasi Toko Pertanian Mutiara Berbasis Website - Hendra Kurniawan Gunawan; Henry Novianus Palit; Kristo Radion Purba (Jurnal Infra, 2018)
Mutiara Agriculture Shop still uses manual process in its operational activities, so much time consuming and prone to error. The owner takes a lot of time in checking the stock of each transaction. The owner can also forget to write a merchant's bill in a receivable book. Mutiara Agriculture Shop has also experienced theft by employees by writing fictitious stock. To overcome these problems, the necessary applications that can support business processes to be fast, precise, and efficient.The work of this thesis focuses on creating a store information system that can help run the business process while minimizing the gap for employees to do corruption. In addition, with up to date reports, help owners quickly and precisely take business decisions.Based on testing that can be done, the application can be used easily and has a fairly complete feature. Applications can be added in the form of graph reports and made more details for the development.[1]    Alatas, H. 2015.  Proyek Membangun Responsive Web Design Dengan Bootstrap 3 Dan 4. Indonesia:Lokomedia.[2]    Idcloudhost Laravel. Retrieved Febuary 1, 2017, fromhttps://idcloudhost.com/pengertian-dan-keunggulan-framework-laravel/[3]    Kumar, S.R., Aravazhi,.. R. 2013. Study on Ajax in Web Applications with Latest Trends. India: Ijritcc.[4]    Larsen, R. 2013. Beginning HTML and CSS. Indianapolis, IN: Wrox[5]    Medi, S. 2012.  Pembuatan Website Sekolah Menengah Pertama Negeri 3 Delanggu, Dengan Menggunakan Php Dan MySQL. Indonesia:ijns.org.[6]    Mitchell, J. 2013. Libjson. England: Author.[7]    Pouncey, I, & York, R. 2011.Beginning CSS: Cascading Style Sheets for Website Design, 3rd Edition. England:Wrox.